1992
DOI: 10.1164/ajrccm/145.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Lung, Chest Wall, and Total Respiratory System Resistances and Elastances in the Normal Range of Breathing

Abstract: We measured total respiratory system and lung and chest wall resistances (Rrs, Rl, and Rcw) and elastances (Ers, El, and Ecw) in awake, relaxed human subjects during sinusoidal volume forcing at the mouth from 0.2 to 0.6 Hz with tidal volumes (VT) of 6 to 18% VC at constant mean airway pressure. In addition, we repeated measurements with the lowest VT at a lower airway pressure and therefore at a lower mean lung volume (Vl). Rrs and Rcw decreased with increasing respiratory frequency (f) and VT, but Rl was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Significant alteration in lung-thorax dynamics is expected to influence both the capnography indices and forced oscillatory data reflecting airway and tissue mechanics (35). The capnogram parameters are determined by the heterogeneity of the lungs, geometry of the airway tree and the forces exerted by the tissue resistive and elastic properties of the lungs and the chest wall (6).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Significant alteration in lung-thorax dynamics is expected to influence both the capnography indices and forced oscillatory data reflecting airway and tissue mechanics (35). The capnogram parameters are determined by the heterogeneity of the lungs, geometry of the airway tree and the forces exerted by the tissue resistive and elastic properties of the lungs and the chest wall (6).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…FOT and interrupter technique both measure R rs , which includes additional resistances of lung and thoracic tissue. Table 1 shows summarized and rounded estimates for fractions of flow resistance from studies on healthy individuals, in which measurements were performed during spontaneous breathing through the mouth at FRC and V T in the sitting position~Bachofen, 1966; Barnas et al, 1992;Ferris, Mead, & Opie, 1964;Hantos, Daróczy, Suki, Galgoczy, & Csendes, 1986;Hyatt & Wilcox, 1961;Jaeger & Otis, 1964;McIlroy, Mead, Selverstone, & Radford, 1955!. 3 The estimates were obtained by different combinations of these techniques with more invasive methods such as the esophagus balloon catheter or pressure recording via a needle inserted into the extrathoracic part of the trachea. Most authors reported a considerable interindividual variation in estimates, probably due to anatomic differences.…”
Section: Comparison Between Methods Of Airflow Resistance Measurementmentioning
confidence: 99%
“…The dynostatic alveolar P/V-curve describes the behaviour of this system during ongoing ventilator treatment. It therefore does not only represent its compliance but is also influenced by its dissipative and elastic components and inhomogeneities, which, in turn, depend on volume, flow and respiratory rate [13,17,18,19]. Thus, it is expected that it will show different features than the traditional static/semi-static methods.…”
Section: Volume-dependent Compliance (Vdc)mentioning
confidence: 99%
“…These methods have only been used as research tools as they require substantial extra equipment and time for measurements and demand an abrupt change of the ongoing ventilator treatment to a special state of flow (no flow or low flow) not encountered during normal ventilator treatment. Such manoeuvres might alter respiratory mechanics from the properties during normal ventilator treatment as compliance and airway resistance are dependent on volume, flow rate and respiratory frequency [13,17,18,19]. We have recently presented a simplified method for measurement of oesophageal pressure (a surrogate for pleural pressure to calculate chest wall compliance) using a liquid-filled, doublelumen stomach tube [20] and the dynostatic algorithm for on-line, bedside calculation of a ªstaticº alveolar P/V-curve under dynamic conditions [21], based on direct measurements of tracheal pressure [22].…”
mentioning
confidence: 99%